Identification and characterization of the LDAP family revealed GhLDAP2_Dt enhances drought tolerance in cotton - Zhao, Yanyan; Duan, Bailin; Liu, Yuxin; Wu, Yuqing; Yu, Dongliang; Ke, Liping; Cai, Fangfang; Mei, Jun; Zhu, Ning; Sun, Yuqiang (Frontiers in Plant Science, 2023)
LD-associated proteins LDAPs play essential roles in tissue growth and development and in drought stress responses in plants. Cotton is an important fiber and cash crop, however, the LDAP family has not been characterized in cotton. In this study, a total of 14, 6, 7, and 7 genes were confirmed as LDAP family members in Gossypium hirsutum, Gossypium raimondii, Gossypium arboretum and Gossypium stocksii, respectively. Additionally, expansion in the LDAP family occurred with the formation of G. kirkii and G. ramondii, which is mirrored in the number of LDAPs found in five Malvaceae species (Gossypioides kirkii, Bombax ceiba, Durio zibethinus, Theobroma cacao and Corchorus capsularis), Arabidopsis thaliana, and Carica papaya. Phylogenetic tree showed that the LDAP genes in cotton can be divided into three groups (Ⅰ, Ⅱ and Ⅲ). Analysis of gene structure and conserved domains showed that LDAPs derived from group Ⅰ (LDAP1/2/3) are highly conserved during evolution, while members from the group Ⅱ and Ⅲ had large variations in both domains and gene structures. Gene expression pattern analysis of LDAP genes showed that they are expressed not only in reproductive organs ovule but also in vegetative organs (root, stem, leave). The expression level of two genes in group Ⅲ, GhLDAP6_At/Dt, were significantly higher in fiber development than in other tissues, indicating that it may be an important regulator of cotton fiber development. In group Ⅲ, GhLDAP2_At/Dt, especially GhLDAP2_Dt were strongly induced by various abiotic stress. Decreasing the expression of GhLDAP2_Dt in cotton via VIGS increased the drought sensitivity and over-expression of GhLDAP2_Dt led to increased tolerance to osmotic-simulated drought stress at the germination stage. Thus we conclude that GhLDAP2_Dt plays a positive role in drought tolerance.